Consumer Attitudes towards Industrial CO2 Capture and Storage Products and Technologies - Valentina Kashintseva; Wadim Strielkowski; Justas Streimikis; Tatiana Veynbender (Energies, 2018)
This paper discusses and elicits consumer attitudes towards industrial carbon dioxide (CO2) capture and storage (ICCS) products and technologies. It presents a comprehensive review of the relevant research literature on consumer attitudes towards ICCS represented by the willingness-to-pay (WTP) and willingness-to-accept (WTA) negative externalities and outcomes of the carbon capture and storage (the so-called “not-in-my-backyard” (NIMBY) approach). In addition, it employs a concise empirical model that uses the data from the online questionnaire survey conducted in 7 European Union (EU) countries with and without ICSS sites. Our results demonstrate that having at least one ICCS site significantly reduces the WTA for the ICCS products and technologies. It is shown that further increase of ICCS sites, including those in the neighboring regions and countries, leads to the increase of negative consumer attitudes to the ICCS technologies and renewable energy policies. It becomes apparent that the majority of consumers are willing to support industrial CO2 capture and storage only if it happens far away from their dwellings. The outcomes of this paper might be informative for the EU local industries and policy-makers who are planning the location of ICCS sites and optimizing the public support for their endeavors. Moreover, they might be relevant for the stakeholders dealing with the threat of climate change and the necessity for the decarbonization of the economy.